2015
DOI: 10.1111/all.12545
|View full text |Cite
|
Sign up to set email alerts
|

Green areas around homes reduce atopic sensitization in children

Abstract: BackgroundWestern lifestyle is associated with high prevalence of allergy, asthma and other chronic inflammatory disorders. To explain this association, we tested the ‘biodiversity hypothesis’, which posits that reduced contact of children with environmental biodiversity, including environmental microbiota in natural habitats, has adverse consequences on the assembly of human commensal microbiota and its contribution to immune tolerance.MethodsWe analysed four study cohorts from Finland and Estonia (n = 1044) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
220
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 33 publications
(52 reference statements)
16
220
2
2
Order By: Relevance
“…It should be noted, however, that associations between green space and allergy are inconsistent, with research in some areas showing that green space is linked to an increased risk of allergy, while similar investigations in other geographic areas show strong protective effects . The latter are corroborated by studies that found associations between increased biodiversity around homes and reduced atopic sensitization (Ruokolainen et al 2015;Hanski et al 2012). This demonstrates the need for more in-depth studies quantifying exposure to pollen, addressing potential confounding and characterizing mechanisms of age-specific adverse and beneficial health effects.…”
Section: Potential Adverse Health Effectsmentioning
confidence: 55%
See 1 more Smart Citation
“…It should be noted, however, that associations between green space and allergy are inconsistent, with research in some areas showing that green space is linked to an increased risk of allergy, while similar investigations in other geographic areas show strong protective effects . The latter are corroborated by studies that found associations between increased biodiversity around homes and reduced atopic sensitization (Ruokolainen et al 2015;Hanski et al 2012). This demonstrates the need for more in-depth studies quantifying exposure to pollen, addressing potential confounding and characterizing mechanisms of age-specific adverse and beneficial health effects.…”
Section: Potential Adverse Health Effectsmentioning
confidence: 55%
“…One hypothesized immunological pathway is exposure to commensal microorganisms in biodiverse natural environments (Rook 2013), which can play an immunoregulatory role. Studies have demonstrated that increased biodiversity in the environment around homes is linked with reduced risk of allergy (Ruokolainen et al 2015;Hanski et al 2012). Greater exposure to commensal microorganisms, especially in the early life, may lead to more diverse skin and gut microbiomes, and provide protection against allergy and autoimmunity (Kondrashova et al 2013).…”
Section: Improved Relaxation and Restorationmentioning
confidence: 99%
“…Age also plays a remarkable role in how important the amenities and affordances of the residential area are to health and well-being (Corraliza et al 2012;Chawla et al 2014;Dadvand et al 2015). Nearby walkable green spaces are reported to promote the health of senior citizens in densely populated urban areas (Takano et al 2002), while children's exposure to green space microbes develops and strengthens their immune system (Ruokolainen et al 2015). Among the age groups, we paid particular attention to children and adolescents (<18 years), and the elderly (>65 years).…”
Section: Measured Socioeconomic-demographic Factorsmentioning
confidence: 99%
“…What this substantial fraction exactly means is a question to which science has no answer and perhaps will never have. However, if we consider all the things species and ecosystems produce to support our everyday life, the list is long: nearly all food, medicines, as well as materials for clothing, manufacturing and construction, never mind the indispensable ecosystem functions, such as the biogeochemical processes without which waste would accumulate and productivity of ecosystems decline, or the recent 'biodiversity hypothesis' according to which the biodiversity in our living environment might protect us against many chronic diseases related to inflammation such as asthma and allergies, autoimmune diseases, many cancers and even obesity and depression (EASAC 2005, MEA 2005, von Hertzen et al 2011, Hanski 2014a, 2016a, 2016d, Ruokolainen et al 2015 Ilkka Hanski was an exceptional natural scientist not only because of his science but also because he was very active in writing for the general public in Finnish. For me personally Ilkka was, and still is, a source of inspiration and this article is founded on two separate but still related pillars inspired by the work of Ilkka.…”
mentioning
confidence: 99%
“…In these writings, Ilkka expressed his acute critique towards the Finnish forest policy and our society in general much more than what can be found from most of his more conventional scientific articles. In addition, these writings, some of which are based on interviews of Ilkka, illustrate that he indeed was not 'only' an ecologist or biologist, but an intelligent clear minded person deeply interested in policy, society and academia (Hanski 1997(Hanski , 2014b(Hanski , 2016a(Hanski , 2016b, human health and future (Hanski 2009b, 2014a, 2016d, Herzen et al 2011, Ilkka Hanski: The legacy of a multifaceted ecologist , Ruokolainen et al 2015, Furman & Hanski 2016, scientometrics and for example the quality of popular science literature translations (Hanski 2003a(Hanski , 2010.…”
mentioning
confidence: 99%